ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH DI LINGKUNGAN KANTOR PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PROVINSI KALIMANTAN TIMUR - -, Dondy Indraprakoso (EKONOMIA, 2019)
The objectives to be achieved in this research is to know the achievement level of maturity of SPIP application as the provision in Indicator of Performance of National Medium Term Development Plan (RPJMN) 2015-2019. The formulation of the problem from this research is "Is the application of Government Internal Control System within the BPKP Representative of East Kalimantan Province has reached the defined stage or is at level 3 as stipulated in the Indicator of Performance of the National Medium Term Development Plan (RPJMN) 2015-2019?".The research is done by library research and research into the field.The hypothesis of this research is "The Maturity Level of GCIS Implementation at BPKP Representative of East Kalimantan Province has reached the defined stage or is in level 3 as the provision in the Performance Indicator of National Medium Term Development Plan (RPJMN) 2015-2019".The analytical tool used is the appraisal instrument as stipulated in the Regulation of the Head of BPKP (Perka BPKP) No. 4 of 2016 on Guidelines for Assessment and Strategy of Increasing Maturity of Government Internal Control System. The instrument refers to the maturity model of COBIT 4.1.The result of this research is that the maturity level of Government Internal Control System at BPKP Representative of East Kalimantan Province has reached the defined stage or is at level 3 so that the hypothesis is accepted.